Health Smart Home with IoT – A State of Art Survey - S.L. , Rakshanasri; J. , Naren; G. , Vithya; S. , Akhil; K. , Dinesh Kumar; S. , Sai Krishna Mohan Gupta (International Journal of Psychosocial Rehabilitation, 2020)
Recent survey estimates that almost over a billion people are found to be disabled which is around quarter the amount of the world’s population. People with disabilities are particularly vulnerable to inadequacies in health care services and hence health care needs for individuals are unmet. Thus the introduction of a home automation technique for people with disabilities who would prefer to remain in the comfort of one’s own home and giving healthcare service is becoming a feasible option. In recent years several projects have been carried out with the aim to ensure better quality of life for disabled patients by applying Internet of things (IoT) in healthcare domain and building an intelligent smart health home. The survey encompasses the complex issues, paucity of diverse techniques proposed for control and monitoring health status systems and a better way to meet the needs of the disabled patients over other techniques.